Influence of uranyl complexation on the reaction kinetics of the dodecane radical cation with used nuclear fuel extraction ligands (TBP, DEHBA, and DEHiBA). Issue 43 (28th October 2021) - Celis Barros, Cristian; Pilgrim, Corey D.; Cook, Andrew R.; Mezyk, Stephen P.; Grimes, Travis S.; Horne, Gregory P.
Abstract : Used nuclear fuel uranium complexants (TBP, DEHBA, and DEHiBA) exhibit significantly different radiation-induced reactivities upon uranyl complexation as dictated by a combination of electron density distribution and reaction pathway energetics. Abstract : Specialized extractant ligands – such as tri-butyl phosphate (TBP), N, N -di-(2-ethylhexyl)butyramide (DEHBA), and N, N -di-2-ethylhexylisobutryamide (DEHiBA) – have been developed for the recovery of uranium from used nuclear fuel by reprocessing solvent extraction technologies. These ligands must function in the presence of an intense multi-component radiation field, and thus it is critical that their radiolytic behaviour be thoroughly evaluated. This is especially true for their metal complexes, where there is negligible information on the influence of complexation on radiolytic reactivity, despite the prevalence of metal complexes in used nuclear fuel reprocessing solvent systems. Here we present a kinetic investigation into the effect of uranyl (UO2 2+ ) complexation on the reaction kinetics of the dodecane radical cation (RH˙ + ) with TBP, DEHBA, and DEHiBA. Complexation had negligible effect on the reaction of RH˙ + with TBP, for which a second-order rate coefficient ( k ) of (1.3 ± 0.1) × 10 10 M −1 s −1 was measured. For DEHBA and DEHiBA, UO2 2+ complexation afforded an increase in their respective rate coefficients: k (RH˙ + + [UO2 (NO3 )2 (DEHBA)2 ]) = (2.5 ± 0.1) × 10 10 M −1 s −1 and k (RH˙ + + [UO2 (NO3 )2 (DEHiBA)2 ]) = (1.6 ± 0.1) × 10 10 M −1 s −1 . This enhancement with complexation is indicative of an alternative RH˙ + reaction pathway, which is more readily accessible for [UO2 (NO3 )2 (DEHBA)2 ] as it exhibited a much larger kinetic enhancement than [UO2 (NO3 )2 (DEHiBA)2 ], 2.6× vs. 1.4×, respectively. Complementary quantum mechanical calculations suggests that the difference in reaction kinetic enhancement between TBP and DEHBA/DEHiBA is attributed to a combination of reaction pathway (electron/hole transfer vs. proton transfer) energetics and electron density distribution, wherein attendant nitrate counter anions effectively 'shield' TBP from RH˙ + electron transfer processes.